Service quality in practice a handbook for practitioners - Murphy, John A. (John Augustine) (Gill and Macmillan, 1993)
This book is intended as a practical handbook, designed for those who want a guidebook to the total service quality approach. It follows the path laid down by the ISO guidelines, in identifying four stages of service quality: identifying what the customer wants, a process that finishes with the production of a service brief, designing the service, converting the service brief into a design specification, delivering the service, having a good specification and putting it into action, and performance analysis and improvement, a philosophy of continuous improvement based on numerical performance measures. The book ends with a chapter on how to implement total service quality. Throughout the book case studies of quality management practice in real Irish service organizations, supplied by themselves, illustrate the points being made. These case studies take up specific problems or aspects of service quality management.